Visible‐Light Photocatalytic Degradation of Methylene Blue Using SnO2/α‐Fe2O3 Hierarchical Nanoheterostructures. Issue 2 (18th December 2012) - Zhang, Shouwei; Li, Jiaxing; Niu, Haihong; Xu, Wenqing; Xu, Jinzhang; Hu, Wenping; Wang, Xiangke
Abstract Three‐dimensional SnO2/α‐Fe2O3 semiconductor hierarchical nanoheterostructures were synthesized for photocatalysis through a low‐cost and environmentally friendly hydrothermal strategy, by crystallographic‐oriented epitaxial growth of SnO2 on three‐dimensional α‐Fe2O3 flowerlike hierarchical nanostructures. In this photocatalyst, visible‐light‐active Fe2O3 flowerlike hierarchical nanostructures were used as a medium to absorb photons and convert them into photogenerated charges, and SnO2 nanoparticles were used as charge collectors to transport the photogenerated charges. The SnO2/α‐Fe2O3 semiconductor hierarchical nanoheterostructures exhibited excellent visible‐light photocatalytic ability for the degradation of methylene blue; this was attributed to the large specific surface area, wide visible‐light absorption range, and efficient electron–hole pair separation properties of the SnO2/α‐Fe2O3 nanoheterostructures. The SnO2/α‐Fe2O3 material showed improved separation of photogenerated electron–hole pairs owing to the potential‐energy differences between SnO2 and α‐Fe2O3, and therefore exhibited enhanced photocatalytic activity. This paper highlights the SnO2/α‐Fe2O3 semiconductor hierarchical nanoheterostructures as potentially more environmentally friendly materials for use in organic pollutant degradation for environmental pollution cleanup operations.